Trends and Prospectsof the Urban Growth in Algeria the state of Batna as a model - Salaheddine AMRAOUI; Sihem OUANASSI; Mustapha AOUFI (Social Sciences Journal, 1970)
This study aims to highlight on the reality of urban growth in Algeria and its future trends and prospects by tracking the process of urbanization and its development through the stages that Algeria has gone through from the colonial period to the present time, where the focus was on the study of urban growth factors, especially the demographic factors represented by the increase in population and rural displacement without forgetting the factor of absence of security during the black decade as well as the development policy of the country and the regulatory factors, Based on a cartographic programmephilcarto and using statistical data to monitor, describe and forecast Algeria's urban growth rates using the demographic spectrum program (spectrum) and studying the state of Batna, in addition to addressing the various effects and secretions left by the rapid pace of urban growth and urbanization on various Algerian cities, which has generated urban and environmental imbalances and crises that have caused obstacles to economic, social and cultural development, as well as the study of the effects of urban growth in Batna, which has also been done at a rapid pace and regular and chaotic ways that have contributed to creating problems in the future expansion of the city and a large consumption of real estate where it has reached the point of total saturation, the subject matter that requires urgent solutions and reconsideration.